Investigating pin-holes issues in Josephson junction travelling waveparametric amplifiers requiring large area of dielectric layer - Navarro Montilla, J; Klimovich, N; Arnaud, B; Driessen, EFC; Tan, B-K (2024)
Microwave superconducting Josephson Travelling Wave Parametric Amplifiers (JTWPAs) exploit the non-linear inductance of a long superconducting metamaterial line formed by thousands of Josephson junctions to achieve broadband parametric gain with quantum limited added noise. Nevertheless, pin-holes in the dielectric (spacer) layer required for fabricating these superconducting transmission lines (STLs) represent a challenge for JTWPAs fabrication. In this paper, we explore two pin-holes mitigation techniques, which shown promising results with DC characterisation of a suite of test structures at cryogenic temperatures. When implemented for actual JTWPA designs with much longer length, they have shown to improve the fabrication yield albeit some pin-holes still seems to exist over the large wafer area. This indicates that further mitigation effort is required to completely eradicate the pin-holes issue for applications requiring large area of dielectric layer such as microwave JTWPAs.